Tobacco cessation program among cab drivers in Mumbai, India: An interventional study - Gauravi Ashish Mishra; Sharmila A Pimple; Vasundhara Y Kulkarni; Subhadra D Gupta; Parishi V Mujmudar (Wolters Kluwer Medknow Publications, 2022)
Background: Tobacco epidemic is one of the biggest public health threats, killing nearly seven million people annually. With implementation of smoke-free public places legislation, cabs in India are smoke free. However, large majority of cab drivers are addicted to tobacco. Aims: The objectives were to measure cab drivers' knowledge, attitude, and practices about tobacco pre and post intervention, educate them regarding hazards of tobacco and need for smoke-free cabs, perform oral cancer screening, and provide assistance to quit tobacco. Subjects and Methods: This interventional study among cab drivers was conducted in Mumbai during 2015-2018. Different cab unions in Mumbai were contacted and 400 cab drivers were enrolled and interviewed. They were offered health education, oral cancer screening, and tobacco cessation assistance at regular intervals for 1 year. Results: About 63.8% of cab drivers used tobacco, mainly in smokeless forms. Almost 94.1% intended to quit, 66.3% had made previous quit attempts, and 69.8% expressed the need of assistance for quitting. One hundred and twelve cab drivers were diagnosed with oral precancers and one with oral carcinoma. About 49.4% of cab drivers quit tobacco and 46.7% reduced tobacco consumption at the end of 1 year. According to multivariate logistic regression analysis, Muslim cab drivers were less likely to quit tobacco as compared to Hindus. Conclusion: Adherence to smoke-free laws plays a significant role in reducing exposure of cab drivers to secondhand smoke. This program demonstrates the successful implementation of tobacco cessation program that could be replicated among other workforces.